2014
DOI: 10.1603/me13122
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and County-Level Distribution of Ticks (Acari: Ixodoidea) in Nebraska Using Passive Surveillance

Abstract: A 100 yr (1911-2011) examination of tick submissions was compiled from the U.S. National Tick Collection and three state databases to determine tick species occurrence in Nebraska Sixteen tick species were identified including Amblyomma americanum (L.), Dermacentor variabilis (Say), Dermacentor albipictus (Packard), Dermacentor andersoni Stiles, Haemaphysalis leporispalustris (Packard), Rhipicephalus sanguineus (Latreille), and Otobius megrini (Dughs). Amblyomma maculatum Koch and Ixodes scapularis Say were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Ixodes scapularis ’ spatial distribution has been studied at various geographic scales in North America [ 16 ]. Some studies reported I. scapularis tick distribution at a broad spatial scale, i.e., sampling sites in different counties or regions of one state [ 18 , 19 , 20 , 21 , 22 ], or sampling sites in the same county [ 23 , 24 , 25 , 26 , 27 ]. Some other studies were carried out at a local scale, i.e., sampling sites in the same city [ 16 , 27 , 28 , 29 ] or in the same forest or park [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ixodes scapularis ’ spatial distribution has been studied at various geographic scales in North America [ 16 ]. Some studies reported I. scapularis tick distribution at a broad spatial scale, i.e., sampling sites in different counties or regions of one state [ 18 , 19 , 20 , 21 , 22 ], or sampling sites in the same county [ 23 , 24 , 25 , 26 , 27 ]. Some other studies were carried out at a local scale, i.e., sampling sites in the same city [ 16 , 27 , 28 , 29 ] or in the same forest or park [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of LD and other TBZ, a passive surveillance approach may involve the collection of tick samples from people or pets or submission of human case reports (e.g., notifiable disease reporting). Passive surveillance can be inexpensive and require less time and labour investment, when compared to other methods [21,22], but can be influenced by population density, as well as the level of effort placed into communication with and education of the public and medical communities [[23], [24], [25]]. A passive approach is well-suited to areas where there is limited information and can be used to establish a baseline of tick and pathogen distribution and monitor for deviations from this baseline [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Passive surveillance is sometimes criticized for under-representation of certain taxa or bias toward certain host associations. However, citizen-submitted tick collections can provide valuable baseline data on prevalence and likelihood of tick encounters ([8284,7]. In fact, there is evidence that passive tick surveillance data is more strongly correlated with reported human cases of tick-borne diseases than active surveillance [7].…”
Section: Discussionmentioning
confidence: 99%